Assessment of phenotypic and genotypic diversity in rice for salinity tolerance at reproductive stage (Bangladesh Journal of Nuclear Agriculture, 2023)
Soil salinity has turned out to be an important global concern, which affects tenable rice production in many agricultural countries like Bangladesh. A cross was made between Binadhan-7 with FL-478 for developing salt tolerant advance lines to assess phenotypic and genotypic diversity in rice for salinity tolerance. Twenty advance rice lines (Binadhan-7/FL-478) along with check varieties were screened for salinity tolerance at reproductive stage using sea site saline water having electrical conductivity (EC) 10 dS m-1. Among the twenty rice lines, seven lines were tolerant, three were moderately tolerant, six were susceptible, four were highly susceptible on the basis of phenotypic evaluation. Seven simple sequence repeat (SSR) markers linked with salt tolerance quantitative trait loci were used for investigation of salt tolerant rice lines. The result revealed that an average number of 6.286 alleles per locus were detected, with polymorphism information content (PIC) values ranging from 0.672 (RM490) to 0.838 (RM562). The highest gene diversity value (0.812) was found in RM562 and the lowest (0.684) was in RM490. A dendrogram constructed from the genetic distance of the genotypes produced four distinct clusters of twenty rice genotypes. Considering both phenotypic and genotypic observation, seven genotypes viz., Binadhan-10, FL-478, SL-51, SL-56, SL-77, EFSD-59 and IZSD-45 were identified as salt-tolerant; on the other hand, EFSD-21, SL-28, SL-32, SL-10, BRRI dhan28, and Binadhan-7 were identified as salt-susceptible. The identified salt-tolerant rice genotypes could be used in the improvement of rice breeding programs.Bangladesh J. Nuclear Agric, 37(2): 1-18, 2023